2018
DOI: 10.1186/s12879-018-3135-4
|View full text |Cite
|
Sign up to set email alerts
|

Airborne geographical dispersal of Q fever from livestock holdings to human communities: a systematic review and critical appraisal of evidence

Abstract: BackgroundQ fever is a zoonotic disease caused by Coxiella burnetii. This bacterium survives harsh conditions and attaches to dust, suggesting environmental dispersal is a risk factor for outbreaks. Spatial epidemiology studies collating evidence on Q fever geographical contamination gradients are needed, as human cases without occupational exposure are increasing worldwide.MethodsWe used a systematic literature search to assess the role of distance from ruminant holdings as a risk factor for human Q fever out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
103
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 59 publications
11
103
0
6
Order By: Relevance
“…These results are consistent with current knowledge that C. burnetii shedding is greater in small ruminants than in cattle regarding the duration of shedding, the bacterial loads in individual samples and the proportion of individual shedders within a herd (EFSA, ). They are also consistent with the fact that sheep or goats, and not cattle, are the likely source of documented human outbreaks (Clark & Soares Magalhaes, ; EFSA, ). However, because the IS 1111 gene (targeted by our qPCR assay as well as by all the qPCR detection kits marketed to date) is duplicated in various numbers depending on C. burnetii strains (Klee et al., ), and because C. burnetii 's genetic diversity is correlated with ruminant species (Joulie et al., ), genotyping studies might prove useful to investigate strain‐specific effects.…”
Section: Discussionsupporting
confidence: 77%
“…These results are consistent with current knowledge that C. burnetii shedding is greater in small ruminants than in cattle regarding the duration of shedding, the bacterial loads in individual samples and the proportion of individual shedders within a herd (EFSA, ). They are also consistent with the fact that sheep or goats, and not cattle, are the likely source of documented human outbreaks (Clark & Soares Magalhaes, ; EFSA, ). However, because the IS 1111 gene (targeted by our qPCR assay as well as by all the qPCR detection kits marketed to date) is duplicated in various numbers depending on C. burnetii strains (Klee et al., ), and because C. burnetii 's genetic diversity is correlated with ruminant species (Joulie et al., ), genotyping studies might prove useful to investigate strain‐specific effects.…”
Section: Discussionsupporting
confidence: 77%
“…Rural location was found to be a significant factor for C. burnetii exposure in veterinarians in the Netherlands (OR 6.6) (Van den Brom et al, ), while studies in Taiwan and Belgium identified rurality to be significant during univariable, but not multivariable, analysis (Chang et al, ; Pozzo et al, ). Globally, the association of rurality with C. burnetii seroprevalence appears to vary and is influenced by land use, geography and seasonal conditions (Angelakis & Raoult, ; Cikman et al, ; Clark & Soares Magalhaes, ; Hackert et al, ; Tozer et al, ). In Australia, rural populations of New South Wales and Queensland report increased C. burnetii seroprevalence and Q fever disease notifications (Gidding et al, ; Islam et al, ; Lowbridge, Tobin, Seale, & Ferson, ; Tozer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, rural populations of New South Wales and Queensland report increased C. burnetii seroprevalence and Q fever disease notifications (Gidding et al, ; Islam et al, ; Lowbridge, Tobin, Seale, & Ferson, ; Tozer et al, ). Rural location may increase exposure to C. burnetii due to the proximity of farms, livestock facilities, and animal transport routes (Clark & Soares Magalhaes, ; O'connor, Tribe, & Givney, ). Geographical dispersal of C. burnetii may also be more pronounced where there are higher densities of wild and domesticated animal species and greater inter‐species interaction, a concept that remains largely understudied (Clark & Soares Magalhaes, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased awareness of possible public health risks related to agricultural production (e.g. living in proximity to farms (Clark and Soares Magalhães 2018;de Rooij et al 2017), a range of food scandals (e.g. mad cow disease, dioxin, horse meat and fipronil) (Meijboom et al 2006;van der Merwe et al 2019) and the impact of farm practices on animal welfare have become issues of broad societal and political debate (Busch and Spiller 2018;Boogaard et al 2011).…”
Section: Introductionmentioning
confidence: 99%